DETERMINASI STATUS GIZI BALITA BERDASARKAN PENGETAHUAN FEEDING RULES, PERILAKU MAKAN DAN KARAKTERISTIK IBU - Yesi Septina Wati; Fatma Nadia; Ary Oktora Sri Rahayu (Institut Kesehatan dan Teknologi Al Insyirah, 2025)
The toddler stage is considered a golden period as well as a critical period in human life. The nutritional issues in Indonesia, with a stunting prevalence of 19.8% in 2024, indicate that the development of eating habits greatly influences the growth and development of toddlers in the future. This study aims to examine the relationship between knowledge of feeding rules, children's eating behavior, and maternal characteristics with the nutritional status of toddlers in the working area of Rejosari Public Health Center, Pekanbaru City. This is a quantitative study with a cross-sectional design. The study population consisted of mothers with toddlers, with a total of 62 respondents selected through purposive sampling. The study was conducted from December 2023 to May 2025. The research instruments included questionnaires, and tools used were a weighing scale and stature meter. Data analysis was performed using the chi-square test with computer assistance. The results showed a significant relationship between children's eating behavior (p-value = 0.022) and the nutritional status of toddlers. However, there was no relationship between maternal education level (p-value = 0.382), income level (p-value = 0.594), and knowledge about feeding rules (p-value = 0.529) with the nutritional status of toddlers in the Rejosari Public Health Center working area. The role of healthcare professionals in providing continuous education in collaboration with nutritionists needs to be strengthened to help improve the nutritional status of toddlers.